2017
DOI: 10.4314/jasem.v21i6.37
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of Methanoilc and Ethanolic Extracts of <i>Citrus sinensis</i> peel (L) Osbeck on Carrageenan induced Paw Oedema in Wistar rats

Abstract: Aqueous ethanoic and methanolic extracts of Citrus Sinensis Peel were investigated for antiinflammatory activity in carrageenan induced paw oedema in wistar rats, and compared to a positive control drug, Indomethacin. These extracts were given(IP) in a concentration of 20, and 70mg/kg with extract with a concentration whichshowed maximum(95%) inhibition on carrageenan induced rat paw oedema. The effect was significantly higher than that of the standard drug indomethacin (93%).Methanol extract with a concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Recently, the anti-inflammatory effect of Citrus sinensis peels' hydroalcoholic and methanol extracts was confirmed by Osarumwense et al (2017). Interestingly, methanol extract was more active than hydroalcoholic extract, and a positive control drug (Indomethacin) with an inhibition of 95% on carrageenan induced rat paw edema at a concentration of 40 mg/kg.…”
Section: Anti-inflammatory Activitymentioning
confidence: 96%
“…Recently, the anti-inflammatory effect of Citrus sinensis peels' hydroalcoholic and methanol extracts was confirmed by Osarumwense et al (2017). Interestingly, methanol extract was more active than hydroalcoholic extract, and a positive control drug (Indomethacin) with an inhibition of 95% on carrageenan induced rat paw edema at a concentration of 40 mg/kg.…”
Section: Anti-inflammatory Activitymentioning
confidence: 96%
“…The antibacterial activity evaluation of the present study showed promising antibacterial activity by ethanol extracts of the peels of C. sinensis against K. pneumonia and E. faecalis, compound 1 against K. pneumonia, compound 2 against P. aeruginosa and K. pneumoni, and compound 4 against S. typhimurium, E. coli and P. aeruginosa and this finding agrees with previous studies by Baba et al (2018). Previous studies by Osarumwense (2017) revealed that the methanolic extract of C. sinensis peel is highly active against Gram positive, Gram negative bacteria and fungi at concentrations of 100 mg/mL, 150 mg/mL and 200mg/mL, respectively. Similarly, a related study by Omodamiro and Jamoh (2014) suggested that ethanolic extracts at different concentrations (250, 125, 62.5, 31.25, and 15.5 mg/mL) exhibited antibacterial activity against S. aureus, S. pneumoniae, E. coli, P. mirabilis and P. aeruginosa, in a dose-dependent manner.…”
Section: Antibacterial Activity 351 In Vitro Antibacterial Activitymentioning
confidence: 99%
“…Antimicrobial activity of P. granatum fruit peels was also reported by Al-Zoreky (2017). Antiinflammatory activity was reported from peels of Citrus sinensis (Osarumwense, 2017), Citrus grandis (Zhao et al, 2019), Punica granatum (Mastrogiovanni et al, 2019) and Ziziphus jujuba (Wang et al, 2019). Citrus grandis peels were rich in coumarins; Punica granatum peels were rich in high molecular weight phenols like alpha and beta punicalagin and low molecular weight phenols like gallic acid, ellagic acid and granatin B; Ziziphus jujuba contained phenolics like quercetin galangin and flavonoids.…”
Section: Issn: 2319-7706 Volume 9 Number 8 (2020)mentioning
confidence: 99%